2010
DOI: 10.1002/gps.2638
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of safety in Alzheimer's patients for intervention with an anti‐hypertensive drug Nilvadipine: results from a 6‐week open label study

Abstract: Nilvadipine was well tolerated by patients with AD. This study supports further investigation of its efficacy as a potential treatment for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In addition, a short treatment duration with nilvadipine in AD patients has been shown to reduce cognitive decline (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a short treatment duration with nilvadipine in AD patients has been shown to reduce cognitive decline (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Among the dihydropyridine CCB tested, we identified nilvadipine for its ability to readily cross the BBB, to lower brain A␤ levels, to improve cognition, and to prevent cerebral blood flow deficits in a transgenic mouse model of AD overexpressing A␤ (18,20). Nilvadipine is a clinically used antihypertensive that we have shown to be well tolerated and to stabilize cognition in AD patients compared with untreated patients (21,22). Interestingly, long term use of nilvadipine in subjects with mild cognitive impairment has also been shown to prevent cognitive decline and to reduce the incidence of AD conversion (23) suggesting that nilvadipine may have disease-modifying benefits.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…In a subgroup analysis of participants with sub-cortical vascular dementia 13 , no significant differences in these adverse events were found, although again the same trend was observed (fewer events in the treatment group). One study was a non-randomized six weeks open label trial including people with dementia into the safety of Nivladipine (CCB) 14 . There was no significant difference in adverse events, but this was a very short period of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Again, no randomised controlled trials have been conducted to examine the relationship between antihypertensive treatment and hypotension in people with dementia. The non-randomised open label trial, which looked at safety of Nivladipine for people with dementia 14 , found no significant difference between treatment and control group in the incidence of orthostatic hypotension.…”
Section: Orthostatic Hypotensionmentioning
confidence: 99%
“…Patients with aMCI who were treated chronically with nilvadipine failed to progress to dementia compared to control subjects [93] and patients diagnosed with AD also maintained clinical stability regardless of pretreatment blood pressure [94]. Treatment with nilvadipine was well tolerated [95]. A phase 3 trial of nilvadipine is currently being conducted in Europe.…”
Section: Resultsmentioning
confidence: 99%